Self-Management of Postnatal Hypertension: The SNAP-HT Trial. Issue 2 (August 2018) - Cairns, Alexandra E.; Tucker, Katherine L.; Leeson, Paul; Mackillop, Lucy H.; Santos, Mauro; Velardo, Carmelo; Salvi, Dario; Mort, Sam; Mollison, Jill; Tarassenko, Lionel; McManus, Richard J.; Crawford, Carole; et al.
Abstract : Hypertension affects 1 in 10 pregnancies, often persisting postpartum, when antihypertensive requirements may vary substantially. This unmasked, randomized controlled trial evaluated the feasibility and effects on blood pressure (BP) of self-management of postpartum hypertension. Women with gestational hypertension or preeclampsia, requiring postnatal antihypertensive treatment, were randomized to self-management or usual care. Self-management entailed daily home BP monitoring and automated medication reduction via telemonitoring. Women attended 5 follow-up visits during 6 months. The primary outcome was feasibility: specifically recruitment, retention, and compliance with follow-up rates. Secondary outcomes included BP control and safety, analyzed on an intention-to-treat basis. Forty-nine percent (91/186) of those women approached were randomized (45 intervention, 46 control), and 90% (82/91) finished follow-up. The groups had similar baseline characteristics. After randomization, BP was lower in the intervention group, most markedly at 6 weeks: intervention group mean (SD), systolic 121.6 (8.7)/diastolic 80.5 (6.6) mm Hg; control group, systolic 126.6 (11.0)/diastolic 86.0 (9.7) mm Hg; adjusted differences (95% confidence interval), systolic −5.2 (−9.3 to −1.2)/diastolic −5.8 (−9.1 to −2.5) mm Hg. Diastolic BP remained significantly lower in those self-managing to 6 months: adjusted difference −4.5 (−8.1 to −0.8) mm Hg. This is the first randomized evaluation of BP self-management postpartum and indicates it would be feasible to trial this intervention in larger studies. Self-management resulted in better diastolic BP control to 6 months, even beyond medication cessation. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02333240. Abstract : Supplemental Digital Content is available in the text.